2019
DOI: 10.1101/560136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibiotic production is organized by a division of labour inStreptomyces

Abstract: 26One of the hallmark behaviors of social groups is division of labour, where different group members 27 become specialized to carry out complementary tasks. By dividing labour, cooperative groups of 28 individuals increase their efficiency, thereby raising group fitness even if these specialized behaviors 29reduce the fitness of individual group members. Here we provide evidence that antibiotic production 30 in colonies of the multicellular bacterium Streptomyces coelicolor is coordinated by a division of lab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 54 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…Actinobacterial genomes readily undergo rearrangements, whereby more than 1 Mb of genomic DNA can be lost [18, 21, 29]. Here, we provide evidence that protoplast formation and regeneration in K. viridifaciens can lead to profound genomic rearrangements in the chromosome as well as loss of (large parts of) the megaplasmid KVP1.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Actinobacterial genomes readily undergo rearrangements, whereby more than 1 Mb of genomic DNA can be lost [18, 21, 29]. Here, we provide evidence that protoplast formation and regeneration in K. viridifaciens can lead to profound genomic rearrangements in the chromosome as well as loss of (large parts of) the megaplasmid KVP1.…”
Section: Discussionmentioning
confidence: 79%
“…By sequencing one revertant that had lost KVP1 we found that this strain had also lost approximately 1.5 Mb of the right arm of the chromosome. Such genetic instability is typical of streptomycetes, and can affect morphological differentiation, but also phenotypic traits associated with natural products, such as pigmentation, antibiotic biosynthesis and antibiotic resistance [20, 21]. Transposable elements were suggested as the principal cause of genetic instability [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations